Metodes vir die Handhawing van Leerderdissipline in die Kenneth Kaunda-streek van Noordwes - Oosthuizen, I. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2010)
Ever since the dawn of a human rights culture in South Africa, learner misconduct appears to be a rising problem in South African schools. Educationalists are still to uncover the most effective methods to deal with learner misconduct – especially after the abolishment of corporal punishment in schools by the South African Schools Act of 1996. Methods to deal with learner misconduct are normally divided in two categories: those methods that prevent learner misconduct and those that are implemented in reaction to learner misconduct. Generally speaking, there is consensus among educational theorists about the fact that the preventative seems to be the more effective educational approach. In this article, the author endeavours to identify the most effective methods applied in secondary schools of the Kenneth Kaunda district in North-West by means of a quantitative survey. An analysis of the responses showed that the respondents preferred the preventative approach to the reactive and punitive. The one exception to this was the punitive approach of the withdrawal of privileges. From a verimax factor analysis the most favoured approach in dealing with learner misconduct appeared to be that of the promotion and advancement of educator professionalism. This and other findings are also discussed from a Christianpedagogical point of view.